(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study examined the effect of wastewater from the sewage plant in Al-Chabaish on the quality of marsh water, which in turn affected the living organisms, especially the fish, which are abundant in these waters. Three stations were selected in the study area. The samples were collected monthly for six months, from March to August 2017. Some of the physical and chemical properties of the Chabaish marshlands were measured. The air temperature ranged between (19-34) ᵒC , water temperature was between (18-33) ᵒC, while the effective phosphate value was between( 0.014 – 0.52) mg / l and the active nitrate between( 0.7 - 4.9) mg / l, sulphate between (570 – 962) mg / l, electrical conductivity was between (3800 – 5860) μs / cm, dissolved oxygen between( 4.7 - 7) mg / l and potassium between( 21.5 – 68) mg /l, while the turbidity was between (24 – 171) mg/l, The total solids suspended were between( 1118 – 3432) mg / l and the pH was( 6.71 - 8.2) , The chloride content was between( 350 – 2000) mg / l, totalhardness between( 200 – 1800) mg / l, calcium between( 48 - 368 )mg /l, magnesium between ( 9.6 - 52 )mg /l and sodium between (430 – 1560) mg /l, While the biological oxygen demand (BOD5 )was( 3.3-5) mg /l. The study examined the effect of wastewater from the sewage plant in Al-Chabaish on the quality of marsh water, which in turn affected the living organisms, especially the fish, which are abundant in these waters. Three stations were selected in the study area. The samples were collected monthly for six months, from March to August 2017. Some of the physical and chemical properties of the Chabaish marshlands were measured. The air temperature ranged between (19-34) ᵒC , water temperature was between (18-33) ᵒC, while the effective phosphate value was between( 0.014 – 0.52) mg / l and the active nitrate between( 0.7 - 4.9) mg / l, sulphate between (570 – 962) mg / l, electrical conductivity was between (3800 – 5860) μs / cm, dissolved oxygen between( 4.7 - 7) mg / l and potassium between( 21.5 – 68) mg /l, while the turbidity was between (24 – 171) mg/l, The total solids suspended were between( 1118 – 3432) mg / l and the pH was( 6.71 - 8.2) , The chloride content was between( 350 – 2000) mg / l, totalhardness between( 200 – 1800) mg / l, calcium between( 48 - 368 )mg /l, magnesium between ( 9.6 - 52 )mg /l and sodium between (430 – 1560) mg /l, While the biological oxygen demand (BOD5 )was( 3.3-5) mg /l.